Tinjauan Kesiapan Guru dalam Mengimplementasikan Kurikulum Merdeka: Studi Kasus SD Islam Swasta Baiturrahman - Zahroh, Nailatus; Setyowati, Dessy; Farisi, Salman Al (Indo-MathEdu Intellectuals Journal, 2024)
The Independent Curriculum was introduced as an effort to increase the relevance of education by focusing on developing student competencies through more contextual learning. This research aims to explore the preparation and experience of teachers in implementing the Independent Curriculum in Baiturrahman Private Islamic Elementary School. This study uses a qualitative approach with case studies as a method to explore deep understanding from the teacher's perspective. Data was collected through in-depth interviews with several teachers who were directly involved in the curriculum implementation process. Data analysis was carried out using a descriptive analysis approach to identify patterns, perspectives, and challenges faced by teachers in implementing the Independent Curriculum. The data analysis techniques used are qualitative data analysis consisting of data reduction, data presentation, conclusion drawing.  The results of the study show that teachers' understanding of the Independent Curriculum varies. Most understand the basic concepts, but some still require additional training. Pancasila student profile learning is well implemented through project and collaborative methods. However, the understanding of 21st century learning needs to be improved. Identifying learners' potential is good, but there are obstacles to curriculum implementation, including a lack of training, resources, and effective communication